2016
DOI: 10.1021/acs.jpcc.6b01041
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Growth, Chemical Activity, and Cluster–Support Interactions for Pt–Re Bimetallic Clusters on TiO2(110)

Abstract: The growth and chemical activity of Re, Pt, and Pt−Re bimetallic clusters supported on TiO 2 (110) have been studied. Pure Re clusters interact strongly with the titania support, resulting in the reduction of the titania surface, and the Re clusters also appear to be partially covered by TiO x at Re coverages as high as 13 ML. Bimetallic clusters can be grown from sequential deposition of Pt and Re in either order at high metal coverages (3.7 ML), where the number of initial nucleation sites is large; in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 96 publications
4
21
0
Order By: Relevance
“…From this perspective, one expects that 153,176,235 layer ~ L exp[-/(kBT)] hk and eq ~ exp[-/(kBT)] hk L 2 for L << L and Lc. (77) Consequently, in this regime * = 2 consistent with results from the analysis for metal (111) surfaces. A more detailed and rigorous analysis of behavior in both regimes follows from a more comprehensive analysis of evolution in configuration space based on the appropriate master equations.…”
Section: Reshaping For Convex 2d Epitaxial Ncs: Fcc(100) Homoepitaxial Systemssupporting
confidence: 84%
“…From this perspective, one expects that 153,176,235 layer ~ L exp[-/(kBT)] hk and eq ~ exp[-/(kBT)] hk L 2 for L << L and Lc. (77) Consequently, in this regime * = 2 consistent with results from the analysis for metal (111) surfaces. A more detailed and rigorous analysis of behavior in both regimes follows from a more comprehensive analysis of evolution in configuration space based on the appropriate master equations.…”
Section: Reshaping For Convex 2d Epitaxial Ncs: Fcc(100) Homoepitaxial Systemssupporting
confidence: 84%
“…Ti­(2p), Sn­(3d), and O­(1s) peaks were fit with Gaussian–Lorentzian (GL) line shapes with values for a full width at half-maximum (fwhm) of 1.7–1.8, 1.9–2.2, and 1.5–1.7 eV, respectively. These parameters are consistent with values in the literature and data previously collected with this XPS system . Based on previously published work, Sn­(3d 5/2 ) spectra were fit with two GL peaks with fwhms of 1.9–2.2 eV , and O­(1s) spectra were fit by two GL components with fwhms of 1.5–1.7 eV. …”
Section: Methodssupporting
confidence: 80%
“…These parameters are consistent with values in the literature and data previously collected with this XPS system. 42 Based on previously published work, Sn(3d 5/2 ) spectra were fit with two GL peaks with fwhms of 1.9−2.2 eV 19,54−56 and O(1s) spectra were fit by two GL components with fwhms of 1.5−1.7 eV. 57−59 LEIS experiments were conducted with 600 eV He + ions, and collection parameters were chosen to minimize beam damage during data collection.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Pt enrichment was solely detected in the top layers of the BNN and correlated to the lower surface free energy of Pt compared to Re, which makes it thermodynamically favorable for Pt to remain at the surface when annealed, whereas Re atoms will diffuse to the bulk. 35 Similarly, it was previously demonstrated that the composition of the top atomic layers in bimetallic nanostructures can be widely modified following their exposure to oxidizing and reducing conditions. [36][37] The changes in the composition of the top layers (~3 nm) are eventually balanced by changes in the bulk composition.…”
Section: Resultsmentioning
confidence: 92%